PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR POS SORONG - Siti Rahma Derlean; Digor Mufti; Munifa Munifa (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this research is to find out how motivation and work discipline influence the performance of employees at the Sorong City Post Office. This research is a quantitative research with a descriptive correlation approach, with the research population being all employees who work at the Sorong City Post Office, using a saturated sampling technique so that the sample used in this research is from the population, namely 26 who work at the Sorong City Post Office. This research data was obtained from questionnaires (primary), field observations. The research instrument uses validity tests and correlation tests. The results of this research show that the partial correlation value between work motivation and work discipline on employee performance is 0.838 in the strong category and the significance value is 0.000 <0.05. This shows that there is a significant positive relationship between work motivation and work discipline on employee performance, meaning that the more motivation and discipline, the higher the employee's performance.